The Impact of COVID-19 on the Hotel Industry and How Owners-Managers are Preparing for a Post COVID-19 Economy in Morocco - Haddar, Manal (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis aims to identify the impact of the COVID-19 on the hospitality industry in Morocco, and how the managers and decision makers are willing to cope with it. The primary objectif of this study is to undertand the impacts of this crisis and thereofore provide recommendations related to sustainable strategic solutions to be applied in Morocco since the primarysource of income in Morocco is the hospitality industry. This study has been conducted in Morocco having owner-managers and decision makers of hotels in Morocco as respondents. A purposeful sampling method was utilized and the distribution network was done via emails, social networking sites and text messages. The results of the analysis revealed that the major challenges confronting the hospitality industry due to COVID-19 are; health and safety concerns, challenges in getting customers, and travel restrictions. According to the results, top management of hotels are preparing for a post pandemic period of operations by providing innovative new products to clients, stressing digitalisations, and by offering reduced rates for attracting more customers. Keywords: Covid-19 pandemic, Post-covid-19, Crisis management, Morocco, Hospitality industry.

ÖZ: Bu tez, COVID-19'un Fas'taki konaklama endüstrisi üzerindeki etkisini ve yöneticilerin bu süreçle nasıl başa çıktıklarını belirlemeyi amaçlamaktadır. Bu çalışmanın temel amacı, Fas ekonomisinin önde gelen gelir kaynağı olan konaklama sektörünün bu krize nasıl tepki verdıği ve çözümler ürettiğini bulmaktır. Bu çalışma, Fas’taki konaklama sektötünde uygulanabilecek sürdürülebilir stratejik çözümlerle ilgili değerli öneriler de sunmaktadır. Araştırmanın alan çalışması Fas'ta gerçekleştirilmiştir, katılımcılar Fas'taki otellerin sahipleri, üst yöneticileri ve departman yöneticileridir. Kullanılan örnekleme yöntemi amaçlı örneklemedir ve dağıtım ağı e-postalar, sosyal ağ siteleri ve metin mesajları yoluyla yapılmıştır. Analizin sonuçları, COVID-19 nedeniyle konaklama endüstrisinin karşı karşıya olduğu başlıca zorlukların; sağlık ve güvenlik endişeleri, müşteri edinmedeki zorluklar ve seyahat kısıtlamaları olduğunu belirlemiştir. Araştırmanın sonuçları,üst yönetime göre salgın sonrası bir döneme hazırlanmak için en etkili çözümlerin; fiyatları düşürmek, yeni ürünler geliştirmek ve dijitalleşmeye hazırlıklı olmak oalrak belirlenmiştir. Anahtar Kelimeler: Covid-19 pandemisi, Post-covid-19, Kriz yönetimi, Fas, Konaklama endüstrisi.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Supervisor: Assoc. Prof. Dr. Mine Haktanır.
Keywords: Tourism; COVID 19 Pandemic-Crisis-Tourism-Travel; Effects of COVID 19-Hotel Industry-Hotels-Morocco; COVID-19-Economic aspects-Morocco; COVID-19 Pandemic, 2020-; Covid-19 pandemic; Post-covid-19; Crisis management; Morocco; Hospitality industry